Addressing Criticisms of Global Religion Research: A Consumption-Based Exploration of Status and Materialism, Sustainability, and Volunteering Behavior - Minton, Elizabeth A. (Journal for the scientific study of religion, 2016)
Religion is a key source of core values and one of the most deeply psychological experiences; however, prior research has often inadequately measured religion's influence on consumption behaviors. Our research addresses criticisms of prior research by (1) reducing cultural bias by conducting research within one country, (2) examining both religious affiliation and religiosity, (3) exploring numerous consumption behaviors (social status desire, materialism views, sustainable behaviors, environmental views, and volunteering behavior) in a within-subjects design, and (4) testing religion's effect on consumption behavior with over 1,000 participants. Findings provide insight for consumer well-being. Specifically, consumers high in external religiosity are more materialistic, more sustainable, and more likely to volunteer than consumers low in external religiosity. Consumers high in internal religiosity are also more likely to be sustainable and hold pro-environmental views. In addition, Buddhists and Hindus are less likely to hold pro-environmental views than Christians. Buddhists are more materialistic than Christians, and Hindus are less desiring of social status than Christians. In addressing the criticisms of prior research in the context of consumption, our research builds on values-based and social-based theories.